Post-myocardial infarction ventricular septal defect. Is it better to operate on a fresh infarction or to wait? A case study - Suder, Bogdan; Janik, Łukasz; Wasilewski, Grzegorz; Konstanty-Kalandyk, Janusz; Sadowski, Jerzy; Kapelak, Bogusław; Ceranowicz, Piotr; Bartuś, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
The authors present case studies of two patients, aged 76 and 77, who were diagnosed with fresh post-myocardial infarction ventricular septal defects (VSD) and were admitted for urgent surgical intervention. The report is a comment in the discussion concerning the optimal time for surgical intervention.